Tahfidz Teachers’ Strategies in Improving Quran Memorization - Daulay, Abdul Sattar; Hasibuan, Safriadi (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2024)
This research was motivated by the Qur'an memorization program at Babur Rohman Islamic Boarding School, Muara Batang Toru District, South Tapanuli Regency, where students were able to memorize the Quran as much as one Juz within two weeks. The purpose of this study was to see how the teacher's strategy in implementing Tahfidz learning in Babur Rohman Islamic boarding school. The type of research used is qualitative research. The method used by research is the descriptive method. A data source consists of two sources: a primary data source and a secondary data source. The data collection techniques used in this study were observation, interviews, and documentation. The results of this study can be concluded that Santri at the Salafiah Babur Rohman Islamic Boarding School, Muara Batangtoru District, South Tapanuli has improved the memorization of the Quran. With Teacher Strategies including: implementing adab-adab tilawah and tahfizul Quran, ablution, memorization targets and organizing tahfidz programs carried out in the classroom and tahfidz programs that are reviewed outside the classroom (extracurricular).